In-suit growth of Cu4SnS4 nanoplates on reduced graphene oxide (rGO) with ligand exchange exhibiting enhanced photodegradation property. (16th July 2022) - Tang, Yu; Liu, Mengmeng; Xu, Hongzhi; Xu, Ming; Zhang, Xiaoyan; Bao, Ningzhong
Abstract: In the present study, a novel Cu4 SnS4 /reduced graphene oxide (CTS/rGO) composite was successfully prepared using a simple one-pot heat-up method. Post-synthetic ligand exchange (LE) and annealing process were performed to further increase the dispersibility and the conductivity of the prepared composite. An unexpected phase transformation from CTS to Cu3 SnS4 with an enhanced absorption in the near-infrared (NIR) region were observed after LE. Furthermore, the photodegradation of Rhodamine B (RhB) by the CTS/rGO composite was investigated. The CTS nanoplates with 10 wt% rGO treated through LE (CTS-10%rGO-LE) exhibited the highest (99.92%) degradation rate of RhB after 90 min of visible-light irradiation, which is approximately 10 and 1.28 times that of the pure CTS and the CTS-10%rGO treated using annealing (CTS-10%rGO-A). The enhancement of the photodegradation activity could be ascribed to the in-suit growth of CTS on rGO and the subsequent LE treatment, which effectively reduced the agglomeration of CTS and increased the electron-transfer ability of the composite materials. The CTS/rGO composite also exhibited high chemical stability of the photodegradation of RhB after four recycles. The electron paramagnetic resonance spectra reveal that ·OH and h + are the main active species in the photocatalytic degradation of RhB with CTS-LE and CTS-10%rGO-LE photocatalysts. The in-suit growth of the CTS/rGO composite with a subsequent LE treatment has the potential to serve as an efficient photocatalysts for the degradation of organic pollutants.